2017
DOI: 10.1111/mcn.12489
|View full text |Cite
|
Sign up to set email alerts
|

Women's dietary diversity in rural Bangladesh: Pathways through women's empowerment

Abstract: The relationship between women's empowerment and women's nutrition is understudied. We aimed to elucidate this relationship by quantifying possible pathways between empowerment and dietary diversity among women in rural Bangladesh. In 2015, we conducted a cross-sectional survey of 2,599 married women ages 15-40 (median: 25) living in 96 settlements of Habiganj District, Bangladesh, as a baseline for the Food and Agricultural Approaches to Reducing Malnutrition trial. We collected data on women's empowerment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 29 publications
3
53
0
Order By: Relevance
“…But, because of the strong correlation between empowerment and nutrition, this dimension is included in the WELI (Sinharoy et al 2018). The findings from the WELI can contribute to exploring this correlation in general and in the framework of livestock.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…But, because of the strong correlation between empowerment and nutrition, this dimension is included in the WELI (Sinharoy et al 2018). The findings from the WELI can contribute to exploring this correlation in general and in the framework of livestock.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…Studies have shown that households with better socioeconomic resources enjoy a more nutritious diet, as opposed to their disadvantaged counterparts whose diet consists of much less fiber, fruits, and vegetables [ 26 , 27 , 28 ]. Households with educated mothers have been shown to have a higher consumption of fruits and vegetables as well as better diet diversity [ 9 , 29 , 30 ]. On the contrary, in some contexts, higher maternal education has also been associated with higher consumption of sugary drinks and more processed foods [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…These new modules include survey questions that have not yet been widely used to measure empowerment: the intrahousehold relationships module (part of core pro‐WEAI) and the optional health and nutrition module (Heckert et al, ; Malapit et al, ; Malapit et al, ). The development of a health and nutrition module is motivated by an increased focus on nutrition‐sensitive agriculture, which aims to address the underlying determinants of malnutrition, often through multisectoral approaches (Ruel, Alderman, & Maternal and Child Nutrition Study Group, ), as well as evidence of the agency‐related pathways by which women's income generation and other enabling resources are related to improvements in women's dietary diversity and nutrition (Sinharoy et al, ; Sinharoy et al, ). Some evaluations of nutrition‐sensitive agriculture programmes have included indicators of women's empowerment related to production and to health and nutrition; however, survey instruments to measure women's empowerment in health and nutrition are not yet widely accepted or rigorously evaluated (Malapit et al, ; Olney et al, ; Ruel, Alderman,, & Maternal and Child Nutrition Study Group, ).…”
Section: Introductionmentioning
confidence: 99%